[OP.7A.08] AWARENESS, TREATMENT AND CONTROL OF HYPERTENSION IN GREECE: INTERIM ANALYSIS OF THE EMENO NATIONAL EPIDEMIOLOGICAL STUDY. (September 2016) - Stergiou, G.S.; Margetaki, A.; Boubouchairopoulou, N.; Haidich, B.; Papachatzi, E.; Chlouverakis, G.; Chatzichristodoulou, C.; Trypsianis, G.; Voulgari, P.; Alamanos, I.; Karakosta, A.; Touloumi, G.
Abstract : Objective: To date no nationwide epidemiological study of hypertension in the general population has been performed in Greece. This study evaluated the prevalence and control of hypertension in a randomly selected general population sample of adults in Greece. Design and method: The EMENO survey (National Morbidity and Risk Factors Survey) supported by the European Social Fund and national funds, is currently performed in Greece, aiming to include 6, 000 adults aged > = 18 years. It is conducted using a multi-stage stratified random sampling method, involving localities throughout the country. Interviewers and physicians made home visits, where medical history, blood sample, and automated blood pressure (BP) measurements were taken (seated position; triplicate measurements; validated electronic upper-arm BP monitors Microlife BPA100 Plus). An interim analysis of participants recruited from 03/2014 to 12/2015 was performed. Hypertension was defined as BP > 140/90 mmHg (systolic and/or diastolic) or diagnosed hypertension under treatment. The prevalence of hypertension was evaluated with statistical methodology taking into account the design and additional adjustments for age and sex. Results: A total of 3, 396 adults were analyzed (1, 455 men [42.8%] and 1, 941 women [57.2%], median age 55.6 years (interquartile range 41.0–68.4 years). BP > 140/90 mmHg (systolic and/or diastolic) was detected in 1, 198 individuals, and 773 were on antihypertensive treatment. Overall 1, 503 subjects were considered as being hypertensives (adjusted prevalence 37.5%, 95% CI 35.5%, 39.5%). The prevalence of hypertension was higher in men (41.5% vs. 33.6% in women, p < 0, 001), and in the elderly (73.3% in subjects > 70 years). Among hypertensive individuals, 40.5% were undiagnosed, 15.7% diagnosed but untreated, 24.5% treated but uncontrolled, and 19.3% were controlled on treatment. Men were more often undiagnosed than women (48% vs. 31%, p < 0.001), and less often controlled (15% vs.24%, p < 0.001). Individuals aged < 60 years had lower rates of hypertension diagnosis and control compared to older ones (p < 0.001). Conclusions: Over 1/3 of the adult general population in Greece has hypertension. About 80% of the hypertensives are uncontrolled, and half of them are undiagnosed. A national program for the detection and control of hypertension in the general population is needed.